2023
DOI: 10.1039/d3nj02339g
|View full text |Cite
|
Sign up to set email alerts
|

A tough, anticorrosive hydrogel consisting of bio-friendly resources for conductive and electromagnetic shielding materials

Abstract: The rapid development of electronic technology requires the use of high performance electromagnetic interference shielding materials to establish a safe environment, and environmentally friendly materials cannot be ignored. This paper...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…The total shielding efficiency (SE) was measured using various scattering parameters (S 11 , S 12 , S 21 , S 22 ) and equation 7 of the Supporting Information, which measures the attenuation of electromagnetic waves passing through the hydrogel . At a frequency of 20 GHz, the AM 20 -Ca 2+ hydrogel displayed a total shielding efficiency (SE) of ∼35 dB (Figure A), which is far exceeding the industrial standard of 20 dB. This value also surpassed that of many other conducting filler-based elastomeric and hydrogel materials used for electromagnetic interference (EMI) shielding applications , , (Table S4). This exceptional EMI shielding ability of the AM 20 -Ca 2+ hydrogel may be attributed to three key factors: high water content (∼74%), a porous network, and adequate ionic conductivity.…”
Section: Resultsmentioning
confidence: 96%
“…The total shielding efficiency (SE) was measured using various scattering parameters (S 11 , S 12 , S 21 , S 22 ) and equation 7 of the Supporting Information, which measures the attenuation of electromagnetic waves passing through the hydrogel . At a frequency of 20 GHz, the AM 20 -Ca 2+ hydrogel displayed a total shielding efficiency (SE) of ∼35 dB (Figure A), which is far exceeding the industrial standard of 20 dB. This value also surpassed that of many other conducting filler-based elastomeric and hydrogel materials used for electromagnetic interference (EMI) shielding applications , , (Table S4). This exceptional EMI shielding ability of the AM 20 -Ca 2+ hydrogel may be attributed to three key factors: high water content (∼74%), a porous network, and adequate ionic conductivity.…”
Section: Resultsmentioning
confidence: 96%
“…Zhou et al 28 prepared a PAM–PVA–GO–LiCl composite hydrogel that exhibited superior anti-dehydration and electromagnetic shielding (EMI) capabilities exceeding 37.2 dB. Xu et al 29 prepared NaCl based PVA-PEG-SA hydrogels, which showed an EMI shielding performance of 32.64 dB. Although the ion-loaded hydrogel showed transparent properties, ion leaching takes place in a normal physiological environment.…”
Section: Introductionmentioning
confidence: 99%
“…35,36 Among carbon nanomaterials, graphene and carbon nanotubes, including their components and composites, are the materials of choice for electromagnetic shielding due to their low density, high conductivity, and corrosion resistance. 37,38 Among them, carbon nanotubes are the most prevalent fillers due to their excellent aspect ratio, high modulus, high electrical conductivity, and mature preparation techniques. Guan et al 39 used cellulose nanofibers (CNFs) and carbon nanotubes (CNTs) to construct hydrogel materials consisting of biologically interpenetrating bi-network of carbon nanotube network and cellulose nanofiber network.…”
Section: Introductionmentioning
confidence: 99%